Social Policy Review 31 : Analysis and Debate in Social Policy, 2019 - Rees, James, 1978-; Heins, Elke; Needham, Catherine, 1974- (Book collections on Project MUSE., 2019)
Bringing together the voices of leading experts in the field, this edition offers an up-to-date and diverse review of the best in social policy scholarship over the past year. It contains vital research, including discussions on the changing landscape of occupational as well as corporate welfare in the UK, the continuing impact of austerity on various social policy areas and the challenges currently faced by the NHS.